A Review on Software-Defined Networking Distributed Controllers (International Journal of Engineering and Computer Science, 2020)
A computer network is a critical issue in our day to day activity; however, today it works under various problems. Since in the current network architecture the control plane and data plane are vertically bundled on the same device. To solve this problem programmable Software-Defined Network is released. OpenFlow is a protocol that vertically separates control plane and data plane of the network devices. In SDN the controllers are the brains of the network that controls the network devices. Today’s network required successful integration of distributed controllers to make the network more consistent. SDN distributed controller is a controller that we can add or remove the controllers according to the number of devices change. Distributed controller architecture has investigated and compared the 6 recent distributed controllers by using 26 criteria. Orion is the first best controller and ONOS is the second best controller.